Anti-glycating and anti-oxidant compounds from traditionally used anti-diabetic plantGeigeria alata(DC) Oliv. & Hiern. - Fadul, Eltayeb; Nizamani, Arsalan; Rasheed, Saima; Adhikari, Achyut; Yousuf, Sammer; Parveen, Shahida; Goren, Nezhun; Alhazmi, Hassan A.; Choudhary, M. Iqbal; Khalid, Asaad (TAYLOR & FRANCIS LTD, 2020)
A new sesquiterpene lactone geigerianoloide (1) and four known flavonoids axillarin (2), quercetin (3), 3-methoxy-5,7,3',4'-tetrahydroxy-flavone (4) and hispidulin (5) were isolated fromGeigeria alata(DC) Oliv. & Hiern. (Asteraceae). Structures were deduced using(1)H- and(13)C- NMR spectroscopy, mass spectrometry, while the structure of compound1was also deduced using X-ray crystallography technique. Geigeria alatais traditionally used for diabetes, therefore compounds were tested for anti-glycation activity, in which compounds2and3showed potent activities (IC(50)values of 246.97 +/- 0.83 and 262.37 +/- 0.22 mu M, respectively) compared to IC(50)value 294.50 +/- 1.5 mu M of rutin. Moreover, compound4exhibited a comparable activity to rutin (IC50 = 293.28 +/- 1.34 mu M). Compound5showed a weak activity. Compounds2,3, and4exhibited potent DPPH radical scavenging activity (IC50 = 0.1 +/- 0.00, 0.13 +/- 0.00 and 0.15 +/- 0.01 mu M, respectively). Compounds2,3, and4demonstrated significant superoxide anion scavenging activity with IC(50)values of 0.14 +/- 0.001, 0.17 +/- 0.00, and 0.11 +/- 0.006 mu M, respectively.
Keywords: Anti-oxidant; Anti-glycation; axillarin; Geigeriaalata (DC) Oliv; & Hiern; Geigerianoloide; GEIGERIA-ALATA; Chemistry; Pharmacology & Pharmacy